Glucocorticoid-induced hyperglycemia (GIH) in pemphigus vulgaris patient at Bangli District General Hospital: A case report - Ni Kadek Setyawati; A. A. I. A. Nindya Sari; Pande Agung Mahariski (Bali Dermatology Venereology and Aesthetic Journal, 2019)
Background: Pemphigus vulgaris (PV) is an autoimmune disease characterized by mucocutaneous blistering and erosion. This is rare, but greatly affects the patient’s life quality and often cause complication of disease and therapy. Hyperglycemia is a complication due to steroid use called glucocorticoid-induced hyperglycemia (GIH). This case report describes hyperglycemia in PV treatment, which later can be a consideration of PV management. Case: A 44-year-old male patient complained of painful lesions on almost the whole body with a form of bullae, erosion, crusting, brittle, the Nikolsky sign (+), and Asboe-Hansen sign (+). The patient was diagnosed with PV. After he had supportive therapy and high-doses of methylprednisolone, his blood sugar is increased. Patients diagnosed by hyperglycemia state due to steroid use, then given insulin as therapy. The patient diagnosed with PV based on history taking and physical examination, but the histopathologic examination wasn’t done due to lack of modality at the hospital. The steroid was given as an immunosuppressive. Be the main therapy for PV, steroids lead hyperglycemia due to disruption of glucose metabolism, thereby increasing insulin resistance in tissues. The diagnosis of hyperglycemia due to steroid use is made in a patient with a normal sugar level before PV therapy. It occurred within the first 1-2 days of therapy. In these patients, diagnosis confirmed by increasing pre-prandial, 2 h post-prandial, and any-time glucose level, after two days methylprednisolone administration. Collaboration with internal medicine colleagues is needed. Conclusion: PV treatment with steroids can induce hyperglycemia, which is dangerous. The understanding mechanism is needed to make early detection and provide therapy properly.